ANALISIS DIGITALISAI PERBANKAN TERHADAP PERUBAHAN PERILAKU TRANSAKSI MENGGUNAKAN PRODUK QRIS - Annisa Syaharani, (2022)
This study analyze about of banking digitalization on changes in customer transaction behavior and customer satisfaction on digital services owned by banks. The objective of this research are to the effect of banking digitalization on customer behavior in transactions and to know customer satisfaction with banking digitalization services. This research uses one of the digital bank product launched by Bank Indonesia that is Quick Response Indonesian Products (QRIS) product. This research identifies the rating of customers using digital banking services that so far these services have meet the factors of customer satisfaction in digital banking services or not. The research method carried out by the author is descriptive analysis in order to get the whole point of view about the effect of banking digitalization to customers behavior and customer satisfaction. Especially for customers that use Quick Response Indonesian Products (QRIS) product for make on payment method in doing tranction activity. The source of this data use primary data and secondary data, data collection came form questionnaire then analyzed. This research will show a sense of customer satisfaction to digitization service owned by banks, as well as advantages and disadcantages felt by customers by banking digitzation services. Kata Kunci : Banking Digitization, Consumer Behavior, Quick Response Indonesia Standards (QRIS) Products, Customer Satisfaction